2009
DOI: 10.1007/s12031-009-9191-x
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Identification of New Genetic Variations as Potential Risk Factors for Alzheimer’s Disease in a Microarray-oriented Simulation

Abstract: Genomic and proteomic studies of neurodegenerative disorders require complementary approaches to integrate the massive amount of data generated in high throughput experimental procedures. We propose a Bioinformatics pipeline in which expression studies guide the selection of candidate genes that should be screened for potential new genetic variations from a public expressed site tags (ESTs) database. Motivated by the former interest of our group in genetic polymorphisms involved with the immune system, we sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…Curiously, this pattern of variations was similar to our previous study in candidate genes for AD (Lemos et al 2009). …”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Curiously, this pattern of variations was similar to our previous study in candidate genes for AD (Lemos et al 2009). …”
Section: Resultssupporting
confidence: 89%
“…The methodology was according to Lemos et al (2009), and the software CLCbio Workbench Combined® version 3.6.2. was used during all the following steps, initially to build spliced ESTs and mRNA files retrieved respectively from the Goldenpath (www.genome.ucsc.edu) and NCBI (www.ncbi.nlm.nih.gov) databases and latter to perform multiples batches of Smith-Waterman BLASTn alignments (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A virtual validation confirmed that some of the variations identified had been reported previously and had been confirmed in DNA samples, showing that this method is a feasible way to detect genetic variations that merit further exploration in genetic risk factor association studies (Colangelo et al. , 2002; Lemos et al. , 2009).…”
Section: Introductionsupporting
confidence: 77%